Incorporação do controle dos gastos ambientais no sistema integrado de gestão de uma indústria siderúrgica: estudo de caso da Arcelormittal Tubarão - Bastos, Mateus Ferreira (2010)
This research has as main objective to propose an alternative use for a ERP tool to generate information that permit incorporation of control of environmental spending on management system in a steel industry. For this, present a literature review with the evolution of environmental issues, the main methods and costing systems and some existing approaches to issue environmental costs. The searched literature supported the theoretical analysis of the costing method in an existing steel plant and how it treats its costs of environmental management. The field research was based on the identification and analysis of the costing method and the environmental management system existing in the steel industry investigated, which led to the development and implementation in a pilot area of an ERP tool capable of identifying spending on environmental management. The results showed that the search dests costing methods are insufficient for analysis of environmental costs and therefore the developing of a tool capable of identifying the costs of environmental management, which hitherto were hidden in the process, became is essential for the incorporation of control of these expenses in the management system of the company studied.